2018
DOI: 10.1002/aenm.201800889
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐Current Triboelectric Nanogenerator Realized by Air Breakdown Induced Ionized Air Channel

Abstract: Air breakdown phenomenon is generally considered as a negative effect in previous research on triboelectric nanogenerators (TENGs), which is always accompanied by air ionization. Here, by utilizing the air breakdown induced ionized air channel, we designed a direct-current triboelectric nanogenerator (DC-TENG) for harvesting contact-separation mechanical energy. During working process, the charges firstly transfer from bottom to top electrode through an external circuit in contact state, then flow back via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…Jianjun Luo et al [57] reported a DC-TENG realized by air breakdown-induced ionized air channel. The structure of the DC-TENG is illustrated in Figure 8a.…”
Section: Mechanical Energy Harvesting Via Air Breakdown 51 Dc-tengmentioning
confidence: 99%
See 1 more Smart Citation
“…Jianjun Luo et al [57] reported a DC-TENG realized by air breakdown-induced ionized air channel. The structure of the DC-TENG is illustrated in Figure 8a.…”
Section: Mechanical Energy Harvesting Via Air Breakdown 51 Dc-tengmentioning
confidence: 99%
“…(i) Charging curve of a 1000-μF capacitor charged by the flexible multilayered DC-TENG (inset shows the photograph of a calculator powered by the charged capacitor). (i-v)The working mechanism of the DC-TENG in stable working state[57].…”
mentioning
confidence: 99%
“…To design effective and efficient PNGs, different kinds of piezoelectric and ferroelectric nanostructures have been reported till date, such as, ZnO nanowires, PZT, BaTiO 3 , GaN nanowire, MoS 2 , Pb free piezoceramic crystals, organic/inorganic lead halide perovskites, nylon nanowire, polyvinylidene fluoride (PVDF) and its copolymer PVDF‐TrFE, PVDF composite and a lots of research work on TNGs have also been reported with different triboelectric materials . Thus, various toxic and non‐biodegradable/biocompatible organic/inorganic/ceramic materials are extensively used to integrate conventional stretchable/flexible portable and wearable electronics which build up smart electronic wastes ( e ‐waste) in huge amount, producing dangerous environmental pollution .…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al designed an ionized air channel created by air breakdown in the separation process to realize an DC output. 18 In 2019, Liu et al reported a newgeneration DC-TENG to power electronics directly, whose charge density is much higher than that of the conventional TENG. 19 However, these DC-TENG usually requires sharp structures to generate arc/spark discharges, which increase the difficulties in fabrication.…”
Section: Introductionmentioning
confidence: 99%